Characterization of bacterial pathogens from egg shell, egg yolk, feed and air samples of poultry houses - Parveen, Arufa; Rahman, Md Mostafizer; Fakhruzzaman, Md; Akter, Mir Rowshan; Islam, Md Shofiqul (Asian Journal of Medical and Biological Research, 2017)
This study was selected to find out the bacterial pathogens in egg yolk, egg shell, feed and air samples of poultry houses at Dinajpur district in Bangladesh with isolation, identification and characterization of bacterial pathogens present in those samples. For this study, a total of 147 samples comprising egg shell (36), egg yolk (36), feed (45) and air (30) were collected during the period from January to May, 2012 and the collected samples were then examined for the bacteriological study by using cultural, morphological and biochemical techniques. On the basis of their cultural, morphological and biochemical properties the isolated organisms were identified as Escherichia coli, Staphylococcus spp., Salmonella serovars and Bacillus spp. In this study it was observed that out of 147 samples a total of 51 were identified as bacterial pathogens in which egg shell containing 10 (27.78%), egg yolk 11 (30.56%), feed 20 (44.44%) and air 10 (33.33%) respectively. In this study it was also observed that the highest prevalence of bacterial pathogens in feed samples (44.44%) in comparison with egg shell (27.78%), egg yolk (30.56%) and air samples (33.33%). In this study it was demonstrated that out of four (04) pathogens Escherichia coli was more abundant (39.21%) in the layer house and its environment in comparison with Staphylococcus spp. (25.49%), Salmonella (23.52%) and Bacillus spp. (11.76%) respectively. Asian J. Med. Biol. Res. June 2017, 3(2): 168-174